The Effects of Transitional Nursing Program from Hospital to Home on Self-Care Behaviors and Readmission Rates among Older Adult Patients with Pneumonia - Whanprarat, Hassana; Hayee, Fusiyah; Siriphan, Siriphan (Princess of Naradhiwas University Journal, 2025)
Background and Objective Pneumonia is a major cause of hospital readmission and mortality among older adults. Transitional care nursing plays an important role in ensuring continuity of care after hospital discharge. This study aimed to examine the effects of a transitional care nursing program from hospital to home on self-care behaviors and readmission rates among older adult patients with pneumonia. Methods This study was quasi-experimental. The participants were 52 older adults who were admitted to a general hospital in southern Thailand. They were divided equally into two groups: an experimental group and a control group, each comprising 26 participants. The research instruments consisted of a transitional care nursing program, a readmission record form, and a self-care behavior assessment tool, which was reviewed by five experts, yielding a content validity index (CVI) of 0.98 and a Cronbach’s alpha coefficient of 0.98. Data were analyzed using descriptive statistics, paired t-tests, independent t-tests, and chi-square tests. Results The findings revealed that the experimental group had significantly higher self-care behavior scores after receiving the program, with statistically significant differences from both their pre-intervention scores and the control group (p < 0.01). Moreover, no participants in the experimental group were readmitted within 28 days post-discharge, whereas the control group had a 15.4% readmission rate. Conclusion and Recommendations The findings of this study indicate that the transitional care nursing program effectively promotes self-care behaviors and reduces hospital readmission rates. It is considered appropriate for implementation in the care of older adults with pneumonia.